Biosynthetic Intermediate Probes for Visualizing and Identifying the Biosynthetic Enzymes of Plant Metabolites. (24th November 2020) - Gao, Lei; Lei, Xiaoguang
Abstract: Plant metabolites play important roles in both plant physiology and drug discovery. Taking advantage of new emerging technologies such as next generation sequencing (NGS), whole genome assembly, bioinformatics, omics‐based strategies have been demonstrated as popular and powerful ways to elucidate complex metabolic pathways in plants. In this viewpoint, biosynthetic intermediates probes have been proposed as the potentinal tools to study the plant natural product biosynthesis via chemical proteomics appoaches or transcriptome analysis. Abstract : See what's missing : Biosynthetic study of plant metabolites paves the way for manufacturing plant‐derived drugs by synthetic biology. However, identifying any missing enzymes in a plant metabolic pathway is a formidable challenge. Biosynthetic intermediate probes make potentially useful tools to resolve the challenge by visualizing biosynthetic enzymes to facilitate transcriptome analysis or chemical proteomics approaches for identifying the biosynthetic enzymes.